2014
DOI: 10.1055/s-0034-1396918
|View full text |Cite
|
Sign up to set email alerts
|

Intertester-Reliabilität der Palpation myofaszialer Triggerpunkte im M. vastus medialis obliquus

Abstract: Zusammenfassung Myofasziale Triggerpunkte sind h?ufig f?r Schmerzen und Dysfunktionen im Bewegungsapparat verantwortlich. Sie stellen ein in der Bev?lkerung sowie der t?glichen Praxis von Physiotherapeuten weit verbreitetes Ph?nomen dar. Ziel der Studie war es, die Intertester-Reliabilit?t der Palpation myofaszialer Triggerpunkte im M. vastus medialis obliquus zu untersuchen. Insgesamt nahmen 27 Probanden an der Untersuchung teil. Die Ergebnisse zeige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Based on research, reproducibility depends on the examiner's experience, muscle depth, and active or latent TrP. Manual detection only differentiates affected muscle from healthy one and does not determine the exact location of TrP [29][30][31][32][33][34][35][36][37][38][39]. Some studies have investigated the morphological characteristics and hemodynamics of TrPs with the objective ultrasound tool and shown that this method can improve the accurate diagnosis and evaluation of TrPs [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Based on research, reproducibility depends on the examiner's experience, muscle depth, and active or latent TrP. Manual detection only differentiates affected muscle from healthy one and does not determine the exact location of TrP [29][30][31][32][33][34][35][36][37][38][39]. Some studies have investigated the morphological characteristics and hemodynamics of TrPs with the objective ultrasound tool and shown that this method can improve the accurate diagnosis and evaluation of TrPs [40][41][42].…”
Section: Introductionmentioning
confidence: 99%